2011
DOI: 10.1002/cncr.25735
|View full text |Cite
|
Sign up to set email alerts
|

Clinical implications of UGT1A1*28 genotype testing in colorectal cancer patients

Abstract: BACKGROUND: Metastatic colorectal cancer is frequently treated with irinotecan, a topoisomerase-I inhibitor. The UGT1A1 gene encodes for an enzyme that metabolizes irinotecan, and its genetic variants were shown to be associated with increased drug toxicity. We evaluated clinical outcomes associated with the UGT1A1*28 variant. METHODS: The study included 329 colorectal cancer patients from the Israeli population-based Molecular Epidemiology of Colorectal Cancer study who were treated with a chemotherapy regime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
50
1
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(55 citation statements)
references
References 19 publications
0
50
1
4
Order By: Relevance
“…In particular, studies have implicated UGT1A1*28 polymorphism with the occurrence of colorectal and breast cancer, while Lacko et al [6] proved its contribution to laryngeal and head and neck cancer [17,24]. Moreover, the incidence of Gilbert's syndrome, an autosomal recessive trait, the genetic basis of which is UGT1A1*28 polymorphism, has been estimated to affect 3-10% of the general population, prevailing in Caucasians over eastern populations, such as Asians and Japanese [6,9].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, studies have implicated UGT1A1*28 polymorphism with the occurrence of colorectal and breast cancer, while Lacko et al [6] proved its contribution to laryngeal and head and neck cancer [17,24]. Moreover, the incidence of Gilbert's syndrome, an autosomal recessive trait, the genetic basis of which is UGT1A1*28 polymorphism, has been estimated to affect 3-10% of the general population, prevailing in Caucasians over eastern populations, such as Asians and Japanese [6,9].…”
Section: Discussionmentioning
confidence: 99%
“…In the promoter region, differences in numbers of TA repeats yield the wild-type 6-repeat allele variant UGT1A1*1 and the mutant 7-repeat variant UGT1A1*28, giving rise to the genotypes WW (TA6/TA6 or *1/*1), MM (TA7/TA7 or *28/*28), and WM (TA6/TA7 or *1/*2). The polymorphism in ERCC1 is found in the fourth exon at codon 118 and is synonymous (Asn118Asn) (Martinez-Balibrea et al, 2010;Shulman et al, 2011). The frequency distributions of the UGT1A1 and ERCC1 alleles in the 89 patients with recurrent ovarian cancer can be seen in Table 1 …”
Section: Genotype Determinationmentioning
confidence: 99%
“…The frequency of UGT1A1 * 28 is high in Caucasians (about 39%) and is considered as a major predictive pharmacogenetic marker of severe hematological toxicity [9,10]. Previous studies reported that the polymorphism of UGT1A1 * 28 is associated with irinotecan-induced severe neutropenia [11,12]. Therefore, in 2005, the U.S. Food and Drug Administration (FDA) suggested that homozygous UGT1A1 * 28 patients should receive an irinotecan dose-reduction by at least one level [13].…”
Section: Introductionmentioning
confidence: 99%